Challenges in clinical training for professional nurse students: A qualitative study - Muhammad Hadi; Rizki Nugraha Agung; Naryati Naryati; Melati Fajarini (Jurnal Keperawatan Padjadjaran, 2025)
Introduction: Clinical training is a cornerstone of nursing education, equipping students with the practical competencies required for professional practice. However, professional nursing students often face significant obstacles, including limited supervision, communication barriers, emotional strain, and resource constraints that hinder their clinical learning. Despite these concerns, few studies in Indonesia have systematically explored these challenges, creating a gap in understanding the specific contextual factors shaping clinical training experiences. Objective: This study aimed to explore the challenges experienced by professional nursing students during clinical training in Indonesia. Methods: A qualitative descriptive study was conducted using semi-structured interviews with 25 professional nursing students from accredited nursing programs in Indonesia. Data collection occurred between March and June 2025 to provide temporal context. Participants were purposively sampled to ensure diverse experiences. Thematic analysis followed Braun and Clarke’s six-step framework, and NVivo software supported data management. Trustworthiness was ensured through credibility, dependability, confirmability, and transferability strategies. Results: Analysis revealed five central themes: (1) Inadequate clinical supervision, characterized by limited instructor availability and insufficient feedback; (2) Communication barriers, including hierarchical dynamics, medical jargon, and language differences; (3) Emotional and psychological strain, stemming from high workloads and performance anxiety; (4) Resource constraints, such as limited access to modern tools and simulation facilities; and (5) Interpersonal challenges, involving peer competition and difficulties in collaborative learning. These issues were further influenced by Indonesia’s cultural and institutional context. Conclusion: Overcoming these barriers requires a holistic strategy encompassing improved student-to-instructor ratios, enhanced communication training, stress management initiatives, investment in educational resources, and fostering positive peer relationships. Institutional dedication to these interventions is critical to advancing clinical training outcomes and cultivating competent nursing professionals.